2008
DOI: 10.1177/003335490812300410
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Risk of Infant Death Based on Florida Birth Records for 2004

Abstract: SYNOPSISObjective. The purpose of this study was to assess the relationship between pre-pregnancy maternal obesity and risk of infant death.Methods. In March 2004, maternal height and pre-pregnancy weight were added to the data collected on the Florida birth certificate. Using birth records linked to infant deaths, these data were used to assess the relationship between pre-pregnancy maternal obesity, as measured by body mass index, and infant death.Results. Pre-pregnancy maternal obesity was associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
(22 reference statements)
2
16
1
1
Order By: Relevance
“…Twelve studies adjusted for potential confounders and 8 adjusted for deprivation or a suitable proxy, but only 5 provided adjusted data suitable for extraction and use in the main metaanalysis (all of which adjusted for by guest on May 12, 2018 http://pediatrics.aappublications.org/ Downloaded from deprivation), although another 3 adjusted using hazard ratios (also adjusted for deprivation) and were subject to a separate, adjusted data metaanalysis. 11,14,15,25,26,[28][29][30]33,39,41,42 Measure of Effect Meta-analysis was performed for obese mothers (BMI $30), mothers with a greater level of obesity (BMI $35), and all overweight or obese mothers (BMI $25). Although 19 studies had extractable data suitable for inclusion in the meta-analysis, only 11 used a consistent BMI definition for the referent group or for obesity; therefore, only these were included in the primary analysis comparing obese and nonobese mothers and the odds of them experiencing an infant death.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies adjusted for potential confounders and 8 adjusted for deprivation or a suitable proxy, but only 5 provided adjusted data suitable for extraction and use in the main metaanalysis (all of which adjusted for by guest on May 12, 2018 http://pediatrics.aappublications.org/ Downloaded from deprivation), although another 3 adjusted using hazard ratios (also adjusted for deprivation) and were subject to a separate, adjusted data metaanalysis. 11,14,15,25,26,[28][29][30]33,39,41,42 Measure of Effect Meta-analysis was performed for obese mothers (BMI $30), mothers with a greater level of obesity (BMI $35), and all overweight or obese mothers (BMI $25). Although 19 studies had extractable data suitable for inclusion in the meta-analysis, only 11 used a consistent BMI definition for the referent group or for obesity; therefore, only these were included in the primary analysis comparing obese and nonobese mothers and the odds of them experiencing an infant death.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…Both of these showed similar pooled effect measures to the primary analysis and are also summarized in Table 1. 11,14,25,26,30 Results of Individual Studies and Synthesis of Results: Narrative Analyses A narrative analysis was undertaken for 5 studies where it was not possible to include their data in the meta-analysis. Two studies were from the United Kingdom, 2 from the United States, and 1 from Jamaica.…”
mentioning
confidence: 99%
“…While it is generally accepted that obesity is associated with adverse health outcomes, studies have also shown that maternal obesity is specifically associated with a variety of pregnancy complications, including labor and delivery difficulties, fetal and neonatal death, maternal hypertension, preeclampsia, and gestational diabetes (Lu et al, 2001), (Bhattacharya et al, 2007), (Thompson et al, 2008). Furthermore, it is possible that maternal obesity might precipitate adverse outcomes that persist through adulthood in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to know this because a form of selection bias could be introduced if cases with missing BMI have different characteristics from controls. Stott-Miller et al [46] included only live birth of women, and it is known that obese women are at risk of fetal death [66]. Therefore, they may have differentially underestimated the true odds of birth defect amongst obese women and thus underestimated the risk.…”
Section: Discussionmentioning
confidence: 99%